Possibilities for the use of tofacitinib in patients with COVID-19 - A. V. Matveev; Yu. Yu. Kiselev; D. A. Sychev (Izdatelstvo OKI, 2020)
No published trials measuring effectiveness of tofacitinib in COVID-19 have been identified. Some professional associations recommend discontinuing tofacitinib if SARS-CoV-2 infections is detected. Taken into account possible complications of the use of tofacitinib (infections, lymphopenia, venous thromboembolism), routine use of tofacitinib cannot be recommended unless within clinical trials under supervision of qualified healthcare professionals.